Supplementary datasets for: Crop wild relatives of the United States require urgent conservation action Version 1.0 - Khoury, Colin K.; Carver, Daniel (International Center for Tropical Agriculture, 2020)
Here we develop a national inventory of CWR of the United States, wherein taxa are classified based on current knowledge of their relation to agricultural crops and their significance as wild food sources. We use occurrence information combined with climatic and topographic data to model the potential distributions of 600 prioritized native wild taxa. We then use ecogeographic tools to conduct preliminary threat assessments and conservation gap analyses for the native CWR. The ecogeographic variation evident in the locations where ex situ conservation samples have been collected, and that evident in species’ ranges distributed within protected natural areas, is measured against the variation found within species’ overall predicted native ranges. Geographic and ecological gaps in current conservation are then identified, providing baseline information for conservation planning, prioritization, and action.